Ethnobotanical study of anticancer plants used in Ugbine, Nigeria and bioactivity-guided isolation of cytotoxic agents from Synclisia scabrida (Miers) ex oliv - Ngozi, Nwaefulu Ogochukwu (2022)
Introduction: Plants are promising source of novel anticancer agents. Although many breakthroughs have been made in cancer treatment, it remains suboptimal. Therefore, alternative therapeutics with novel mechanisms of action, with minimal side effects and costs are urgently needed. Method: Structured questionnaires were used for the ethnobotanical study. The ground whole roots and leaves of Synclisia scabrida (Miers) ex Oliv (SS) and leaves of Petiveria alliacea L. (PA) were sequentially and separately extracted using a solid–solvent ratio of 1:2, of hexane, dichloromethane, ethyl acetate, methanol, or dichloromethane: methanol (1:1), by cold maceration for 72 h followed by another cold maceration for 24 h. The extract was filtered, concentrated at 40°C with a rotary evaporator and further dried in the oven set at 40°C to obtain crude extracts, which were stored in a refrigerator. A preliminary phytochemical analysis of SS whole root methanol extract was carried out. MTT cell viability assay was employed to evaluate the cytotoxicity potential of the extracts/compounds in colon (HCT-116), prostate (PC-3), breast (MCF-7), pancreatic (PANC-1) cancer cells and human normal lung (BEAS-2B) and murine microglial (BV- 2) cells. Cell cycle distribution of treated PANC-1 was analysed by flow cytometry for understanding of the mechanism behind the observed anticancer potential of SS. Using a bioassay-guided approach, the most active extract/fraction were purified to yield 4 active compounds (SS_C1, SS_C2, SS_C3 and SS_C4). The structures of SS_C2 and SS_C4 were successfully characterised using 1H, 13C-NMR, COSY, HMBC, HSQC, FTIR and LC/MS Q-TOF spectroscopy. The compounds’ molecular targets were predicted using in silico molecular docking and molecular dynamic approaches. Results: The ethnobotanical study revealed the use of SS and PA for cancer treatment. Phytochemical screening of the methanol extract confirmed the presence of alkaloids, tannins, flavonoids, steroids, and fixed oil. The methanol extract had the following IC50 (μg/mL) in cancer cell lines: HCT-116 (23.3 ± 10.4), MCF-7 (35.0 ± 5.0), PC-3 (29.3 ± 11.0) and PANC-1 (5.7 ± 1.2). SS induced a dose-dependent arrest of PANC-1 cells in the S phase. Structure elucidation of SS_C2 and SS_C4 revealed they are bisbenzylisoquinoline alkaloids. Both compounds were identified as close analogues of cosculine and cycleanine, respectively. SS_C2 (IC50 = 46.7 ± 5.8 μg/mL; SI = 2.1; P<0.000) and SS_C4 (IC50 = 41.7 ± 7.6 μg/mL; SI = 2.4; P<0.000) were selectively toxic towards HCT-116 and MCF-7, respectively. The selectivity was far greater than that of gemcitabine, which showed higher toxicity to normal lung cells (BEAS-2B). The in silico molecular dynamic simulations results showed RMSF plots of PARP1–ligand complexes were more stable than the apo protein. This shows a very high PARP1-ligand complexation stability, suggesting that both ligands (SS_C2 and SS_C4) are potential PARP1 inhibitors. Conclusion: SS_C1 was active against colon and pancreatic cancers, SS_C2 was selectively active against colon cancer while SS_C4 had the best selectivity towards breast cancer cells. SS_C2 and SS_C4 are new bisbenzylisoquinoline alkaloids, and potential PARP1 inhibitors which could become leads for the development of targeted therapy for the treatment of colon, breast, and pancreatic cancers.